The Subjective Costs of Health Losses due to Chronic Diseases - Ada Ferrer-i-Carbonell; Bernard M.S. van Praag (Tinbergen Institute, 2002)
This paper proposes a method to evaluate health losses or gains by looking at the impact on well-being of a change in health status. The paper presents estimates of the equivalent income change that would be necessary to change general satisfaction with life to the same extent as a change in health satisfaction would do. In other words, the income equivalent of health satisfaction changes is estimated. Next, this health satisfaction changes are linked to specific diseases in order to estimate the income equivalent for these diseases. This method uses answers to well-being and health satisfaction questions as posed in a large German data set, distinguishing between orkers and non-workers and between East and West Germans. It is found, for instance, that for West-German workers hearing impediments are on average equivalent to an income reduction of about 20%, and that heart or blood difficulties are for the same group equivalent to a 47% income reduction.
Keywords: 330; chronic diseases; equivalent income; health damages; health satisfaction; well-being; Krankheit; Lebensqualität; Theorie